Borders and Healthcare: Medical Mobility, Globalization and Borderlands Tourism - Cuevas Contreras, Tomas Jesus (Routledge/Taylor & Francis, 2022)
At first glance, the crossover between tourism and the practice of medicine seems to be an incongruous fit, perhaps even contradictory or oxymoronic. This is largely owing to the common misunderstanding that “tourism is a frivolous pursuit: fun, sometimes educational in the lightest sense, often romantic, even exotic”